Pengaruh Penambahan Gliserin dan Polivinil Alkohol Terhadap Karakteristik Biofoam dari Kulit Singkong dan Daun Angsana - Putri , Melysa; Kemala Putri , Dwi; Putri , Alvernia (REACTOR: Journal of Research on Chemistry and Engineering, 2021)
Styrofoam is a petroleum-based and synthetic polymer that is only used once. To reduce waste and environmental damage as well as health problems, this study aims to make Biofoam from cassava peel and angsana leaves using a combination of extrusion and baking methods. In this study, glycerin and polyvinyl alcohol were also added with volume variations, 10: 30 (sample 1), 20 : 20 (sample 2), and 30: 10 (sample 3) mL to improve the physical properties of Biofoam. The physical characteristics observed were color, water content using the gravimetric method, and water absorption capacity of ABNT NBR NM ISO 535. Sample 1 and sample 2 were lighter in color than sample 3. The lowest water content value was found in sample 2, while sample 2 was has the ability to absorb less water is sample 3.